Transatlantic links and BRICS: prospects of strategic co-existence - E. R. Voronin (Vestnik MGIMO-Universiteta, 2013)
The article analyzes the possibilities of building long-term relations between the Western intergovernmental organizations, first of all, NATO and the European Union, and BRICS, considers the prospects for the strategic co-existence between them. Considering the commitment of the countries of the BRICS the norms and principles of international law, the author believes that the central place in the agenda of their relations with the United States and the West in general can take the task of expanding the legal framework of relations between them, the further development of the practice of the decision of the international problems solely on a legal basis.